Masculinization of Tilapia (Oreochromis Niloticus) by Oral Method Using Senggani Fruit Extract (Melastoma Malabathricum L.) - Akbar Marzuki Tahya; Muhammad Safir; Nopita (LPPM Universitas Tadulako, 2024)
Introduction: Tilapia have different growth rates in male and female fish where the growth of male fish is faster than female. Therefore, in tilapia farming activities, the production of tilapia weighing >100g/head is difficult to achieve due to uncontrolled spawning. Method: This study was designed using a completely randomized design (CRD) with 5 treatments and 4 replicates, namely treatment A (control), B (Senggani fruit extract 0.75 g/kg feed), C (extract 1.5 g/kg feed), D (extract 2.25 g/kg feed), E (extract 3 g/kg feed). The organisms used in the study were 7-day-old tilapia larvae. Tilapia larvae were given feed that had been added with Senggani fruit extract according to the treatment dose. Tilapia were reared for 62 days, and given artificial feed containing 41% protein, each feeding was given with a frequency of 3 times a day (morning, afternoon, evening). Results and Discussion: The results showed that the highest percentage of male sex was found in treatments A, B, C, D and E, which amounted to 50; 56.25; 57.5; 58.75; and 60%, respectively. Daily growth rate, survival and feed conversion ratio obtained during the study in each treatment amounted to 7.49, 7.45; 7.44; 7.46; and 7.40. for survival 73.75; 72.5; 72.5; 70; and 68.75 then the results of feed conversion ratio respectively 1.86; 1.88; 1.89; 1.86; and 1.91. The analysis showed that the highest percentage of male sex was found in the treatment of 3 g/kg feed which amounted to 60% (P>0.05). Daily growth rate, survival rate and feed conversion ratio did not significantly affect the treatment given (p>0.05). Conclusion: The results of water quality measurements obtained are still within the optimum limits for tilapia rearing. Conclusion: Feeding using Senggani fruit extract to masculinize tilapia did not have a significant effect (p>0.05) on the percentage of male tilapia, daily growth rate and feed conversion ratio.